Pengaruh Perputaran Piutang dan Perputaran Persediaan Terhadap Roa pada PT Bank Mandiri Tbk - Putri Gami, Emelia Rahmadany (Lembaga Komunikasi dan Informasi Dosen, 2022)
The purpose of this study was to find out whether there was an influence of accounts receivable turnover and inventory turnover to roa at PT. Bank Mandiri Tbk period 2011 to 2018. The method used in this study was a quantitative method with multiple linear regression analysis techniques. The data used were secondary data, hypothesis testing using the test of the coefficient of determination (R2), Simultaneous Test (F) and partial test (t) by calculation using the SPSS program. The results showed that partially Accounts Receivable Turnover has a significant effect on ROA. While Inventory Turnover has not a significant ROA effect on PT. Bank Mandiri Tbk, while simultaneously Receivable Turnover and Inventory Turnover has not a significant effect on ROA at PT. Bank Mandiri Tbk. Keywords: Accounts Receivable Turnover, Inventory Turnover, and ROA.